La doctrina industrialista de Carlos Pellegrini - Popescu, Oreste (2014)
The author presents a global view of the literature on Carlos Pellegrini (1846-1906) with special reference to Pellegriní's doctrine of industrialism developed as a member of the school of thougllt that was led by Vicente Fidel López (1815-1903). He considers the relation of Pellegrini's ideas with E.C. Carey's and Federico List's theories as well as the influence of Emilio de Alvear's (1817-1882) and Enrique Richelot's (1811-1864) work. The study also refers to the XXth century ecunomists Alejandro Bunge (1880-1943) and Raúl Prebisch (1901-1986).